2008
DOI: 10.1007/s12199-008-0040-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of hypertension with changes in the body mass index of university students

Abstract: Background There are few longitudinal studies on the associations of obesity with hypertension in young adults. Objectives To analyze longitudinally to what extent weight gain associates with hypertension in young adults. Methods The subjects of this study consisted of 6,178 university students (male 4,098; female 2,080). The associations of hypertension with body type change were longitudinally examined by using the records of health examinations while at university. The prevalence ratios (PRs) for hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
8
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
(47 reference statements)
6
8
0
1
Order By: Relevance
“…The prevalence of hypertension in this age group found in our study was similar to study by Dores et al 14 prevalence when compared to our study. [22][23][24][25][26][27][28] Similar studies conducted by Al Majed et al and Kanade et al found higher prevalence in this age group. 29,30 The National Health and Nutrition Survey for the year 2012-2013 reports that the prevalence of hypertension in young adults of United States to be 7.3%, this prevalence is also lower than our study.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The prevalence of hypertension in this age group found in our study was similar to study by Dores et al 14 prevalence when compared to our study. [22][23][24][25][26][27][28] Similar studies conducted by Al Majed et al and Kanade et al found higher prevalence in this age group. 29,30 The National Health and Nutrition Survey for the year 2012-2013 reports that the prevalence of hypertension in young adults of United States to be 7.3%, this prevalence is also lower than our study.…”
Section: Discussionsupporting
confidence: 60%
“…Another study conducted by Uchiyama et al among university students also found a significant relationship between overweight or obese category and hypertension among both males and females (p<0.05). 26 Further, among senior year males being underweight was found to be protective with an odds ratio of 0.55 (0.34 to 0.99). In our study, we did not attain the significance level for underweight category.…”
Section: Discussionmentioning
confidence: 90%
“…La tercera parte de los participantes mostró sobrepeso u obesidad predominantemente en el grupo femenino, lo cual fue un hallazgo diferente a lo clásicamente reportado como en las series descritas por Palomo et al (23) y Uchiyama et al (25), en grupos comparables. Al respecto postularíamos el sedentarismo como un precursor determinante.…”
Section: Discussionunclassified
“…Many studies have highlighted obesity as an important factor for prehypertension and hypertension (6,7,9,11,(15)(16)(17)(18). Based on the Asian BMI categories, our results show that 11.7% of all the students were obese; this also demonstrated significantly that the highest proportion of prehypertension was found in students with BMI ≥ 25, rather than in their normotensive counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Factors associated with prehypertension or hypertension among university students included sociodemographics [male gender (9,11,12,14), greater age (11) and hypertensive first-degree relatives (14)], BMI obesity (6,7,9,11,(15)(16)(17)(18), substance use [smoking (7,9) and heavy alcohol use (19)], and in young women taking oral contraceptives (14). In addition, among general adults, factors associated with prehypertension or hypertension included physical inactivity (20,21), excess sodium intake (20), inadequate fruit and vegetable consumption (FVC) (20), psychosocial stress [posttraumatic stress disorder (PTSD) (22), depression (23) and short sleep duration (24,25)], and poor sleep quality (25).…”
Section: Introductionmentioning
confidence: 99%